An investigation of the case on students failing Aural Skills and Theory of Music among diploma students in Universiti Teknologi MARA (UiTM) / Nur Azreena Abdul Aziz - Abdul Aziz, Nur Azreena (Faculty of Music, 2016)
This research was accomplished in September 2015 - January 2016. This study examines student's perceptions on failing Aural Skills and Theory of Music subjects among Univeriti Teknilogi MARA music students. This study is focused on the music students from Diploma of Music department (MU110) only. This research was proposed to give benefit for the diploma music students regarding failing two core subjects, which are Aural Skills and Theory of Music. There are three main objectives of this study, 1) to investigate the causes on why music students in UiTM Shah Alam are failing Aural Skills and Theory of Music, 2) to determine the effects if the students fail in theory and aural skills subjects and 3) to propose the solutions on how to improve their aural skills and theory subjects among diploma students in the Faculty of Music, UiTM Shah Alam. The survey questionnaires were distributed thirty (30) diploma students that are currently started their semester. The data collected were analyzed using Microsoft Excel to calculate the numerical data obtained from the distribution of questionnaires. In findings, it is shown that majority of the students do experienced poor results in either Aural Skills or Theory of Music during their studies. In addition, the other findings was obtained during this research is that one of the factor on why the students are failing either subject was their attendance to class. Thus, skipping classes' effect the students getting bad grades in their exam and loss focus in class. Plus, the solution to improve both aural and theory are to ask more questions to lecturers or friends, do lots if ear training and theory exercises and avoid skipping classes. The whole study concluded that it is able to detect the main problem that causes UiTM music student failed these subjects and show the effect of it and also the solution to improve the problem faced by the students.